2013
DOI: 10.1111/jfd.12128
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RAPDSCAR marker linked to white spot syndrome virus resistance in populations of giant black tiger shrimp, Penaeus monodon Fabricius

Abstract: White spot disease (WSD) caused by white spot syndrome virus (WSSV) creates severe epizootics in shrimp aquaculture industry worldwide. Despite several efforts, no such permanent remedy was yet developed. Selective breeding using DNA markers would be a cost-effective strategy for long-term solution of this problem. In the present investigation, out of 30 random primers, only one primer produced a statistically significant (P < 0.01) randomly amplified polymorphic DNA (RAPD) marker of 502 bp, which provided a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Previously, a prevalence study has been performed among the different important coasts along the east coast of India namely Digha, West Bengal; Chilika, Orissa; Visakhapatnam, Andhra Pradesh; and Chennai, Tamil Nadu. Similar observation with the current study was found except for Digha and Chennai (Dutta et al., ). This disparity in the result may be due to, in the previous study, shrimp samples were collected throughout the year, not in a particular season.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previously, a prevalence study has been performed among the different important coasts along the east coast of India namely Digha, West Bengal; Chilika, Orissa; Visakhapatnam, Andhra Pradesh; and Chennai, Tamil Nadu. Similar observation with the current study was found except for Digha and Chennai (Dutta et al., ). This disparity in the result may be due to, in the previous study, shrimp samples were collected throughout the year, not in a particular season.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a 457 bp DNA marker developed by RAPD‐SCAR method was also found in P. monodon , which is mostly present in the disease‐resistant shrimp. WSSV challenge experiment to prove its significant association with disease resistance showed 2.25 × 10 3 fold lower WSSV propagation occurred in disease‐resistant shrimp populations (Dutta et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of SCAR and RAPD has significantly improved the stability and authenticity of the technique (Dnyaneshwar et al, 2006;Su et al, 2007;Li et al, 2010;Kumla et al, 2012;Rajesh et al, 2013;Fu et al, 2013;Noormohammadi et al, 2013;Mei et al, 2014a,b). Previous studies successfully developed RAPD markers for different species of animals, plants, and microbes (Lee et al, 2013;Yang et al, 2013Yang et al, , 2014Dutta et al, 2014). However, no SCAR marker for the identification of different Ganoderma species has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Norwegian scientists initiated the study of resistance-related MHC genes in Atlantic salmon [95] . Rodriguez-Ramilo et al found an anti-ciliate related SSR marker, Sma-USC256, in turbot [96] and Duttaet et al found a RAPD-SCAR marker related to white spot disease (WSD) resistance in Penaeus monodon, and subsequently identified another 71bp SSR marker associated with WSD [97,98] . In rainbow trout, Campbell et al isolated SNP markers related to bacterial cold water disease and infectious hematopoietic necrosis virus [99] .…”
Section: Disease Resistance-related Markersmentioning
confidence: 99%